Membangun Budaya Literasi Baca di UPT SD Inpres Bert Kaluku Bodoa - Syamsul Alam; Nurhadifah Amaliyah; Mutmainna Mutmainna; Fitriani Fitriani; Sri Wulandari (Empowerment: Jurnal Pengabdian Masyarakat, 2023)
schools in carrying out reading literacy at the Inpres Bert Kaluku Bodoa Elementary School. Reading is an important thing in the teaching and learning process. Reading is the process of absorbing knowledge through reading or writing. Each student has abilities that vary from fast, medium and slow in terms of reading. This study aims to increase the need for habituation in students in increasing interest in reading. future at SD Inpres Bert Kaluku Bodoa. With some data and documenting the results of "learning while learning" making a reading corner in class. The object of the research is the class teacher and students in grades V and a reading corner in the library with data collection techniques by direct observation, interviews and documentation. The data obtained were analyzed qualitatively, showing that the first reading corner activity was an evaluation program at the Inpres Bert Kaluku Bodoa Elementary School. Second, the implementation of reading corner activities is carried out every day